An Ethnobotanical Study of Nutraceutical Plants in Kolokuma Local Government Area Bayelsa State, Nigeria - Inala, Eneni R. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2025)
Background: This study aimed to document the ethnobotanical knowledge of nutraceutical plants among residents of Kolokuma Local Government Area, Bayelsa State, Nigeria. It focused on traditional uses, nutritional and medicinal properties of these plants, and their potential integration into modern healthcare and nutrition systems. Methods: Data were collected from 150 respondents across three communities using semi-structured questionnaires. The data were analyzed using descriptive statistics and frequency distributions to assess local knowledge, practices, and perceptions. Results: The findings showed that 80% of respondents confirmed the use of nutraceutical plants in their locality. While 60% acknowledged the existence of documentation methods, 66.67% reported that traditional knowledge was primarily transmitted through oral traditions. Nutritional and medicinal benefits were affirmed by 86.67% and 73.33% of respondents, respectively. Although interest in integrating these plants into modern healthcare practices was high, only limited application in current nutritional practices was reported. Conclusion: The study revealed a strong base of traditional knowledge and widespread use of nutraceutical plants in the study area. However, gaps in formal documentation, inconsistent knowledge transfer, and limited sustainable harvesting practices were identified. It is recommended that improved documentation systems be developed, sustainable harvesting be promoted, and traditional knowledge be integrated into healthcare education. Collaboration among traditional practitioners, researchers, and modern healthcare professionals is also advised.